Delayed anaphylaxis following propofol infusion in unknown egg allergic patient - Laoutid, Jaoaud; Bibiche, Lotfi; Jbili, Nabil; Chkoura, Khalid; Hachimi, Moulay Ahmed; T, Africha (International Journal of Medical Research and Review, 2017)
We report a case of anaphylaxis that occurs more than one hour after propofol administration for colonoscopy. The patient did not reveal his allergy to egg in the preoperative evaluation. Administration of propofol to patient with egg allergy should be avoided.